Construction estimates : from take-off to bid - Foster, Norman; Trauner Jr., Theodore J.; Vespe, Rocco R.; Chapman, William M. (McGraw-Hill, New York, 1995)
The third edition contains all of he take-off examples and general text of the first and second editions - plus expanded treatment of the general estimating procedures, pricing of general conditions and overhead, new take-off techniques for masonry, and most important the complete drawings, specification data, take-off and priced estimate of a $660,000 building. The pricing has been updated to reflect current prices.
General methods and procedures -- Excavation and site work -- Concrete -- Reinforcing steel --Masonry -- Carpentry -- Job overhead -- Subcontractors' bids -- Industrial building -- Industrial building-The estimate -- Pricing the estimate.
Includes index.
Keywords: BUILDING ESTIMATE; BUILDINGS CONSTRUCTION ESTIMATION